2021
DOI: 10.1088/1757-899x/1094/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Sawdust to Cement on its Thermal Conductivity and Compressive Strength

Abstract: In this practical study, the thermal conductivity and compressive strength of a number of cement mortar and sawdust mixtures were measured. This study aims to analyze the possibility of using these mixtures as thermal insulators in the building parts. The materials used in the study were ordinary Portland cement available in the local Iraqi market, sand, and sawdust. Samples were prepared according to American standards. Sawdust in two different sizes (greater than 50 mm and less than 1.4 mm) was added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The experiments showed that the compressive strength of the concrete decreased with an increasing wood chip content. Hafidh et al [ 12 ] and other scholars [ 13 , 14 ] have also reported similar findings. Fadiel et al [ 15 ] prepared wood concrete by replacing fine aggregate by volume with wood chips at different replacement levels of 5%~50% and proposed a formula for estimating the compressive strength based on the wood chip content.…”
Section: Introductionsupporting
confidence: 74%
“…The experiments showed that the compressive strength of the concrete decreased with an increasing wood chip content. Hafidh et al [ 12 ] and other scholars [ 13 , 14 ] have also reported similar findings. Fadiel et al [ 15 ] prepared wood concrete by replacing fine aggregate by volume with wood chips at different replacement levels of 5%~50% and proposed a formula for estimating the compressive strength based on the wood chip content.…”
Section: Introductionsupporting
confidence: 74%
“…Additional research has demonstrated that the thermal conductivity of concrete mixes can be reduced by incorporating wood waste [13][14][15][16]. Moreover, Ahmed et al [17] recommended the use of sawdust-based concrete to improve the energy efficiency of buildings.…”
Section: Wood-based Concretesmentioning
confidence: 99%
“…Relevant studies [26] have shown that the noise of particleboards prepared using wood and cementitious materials is in the range of 32-100 Hz, and the thermal conductivity is 0.29 Wm −1 K −1 . In addition, wood with different particle sizes contributes differently to the thermal-insulation effect [27]. In summary, the application of waste wood in construction engineering can have a significant contribution.…”
Section: Introductionmentioning
confidence: 99%